Adjusting Local Molecular Environment for Giant Ambient Thermal Contraction. Issue 23 (18th May 2016) - Shen, Xingyuan; Connolly, Timothy; Huang, Yuhui; Colvin, Michael; Wang, Changchun; Lu, Jennifer
Abstract : A low‐energy triggered switch that can generate mechanoresponse has great technological potential. A submolecular moiety, S‐dibenzocyclooctadiene (DBCOD) that is composed of a flexible eight‐membered ring connecting to a phenyl ring at each end, undergoes a conformational change from twist‐boat to chair under a low‐energy stimulus such as near infrared irradiation, resulting in thermal contraction of DBCOD‐based polymer. Experimental evidence corroborated by theoretical calculations indicates that introducing molecular asymmetry can reduce crystallinity significantly and consequently facilitate the kinetics of the conformational change. It has been demonstrated that the negative thermal expansion (NTE) coefficient of a DBCOD‐based polymer system can be adjusted in a range from −1140 to −2350 ppm K −1 . −2350 ppm K −1 is ≈10 times better than the value reported by the second best NTE system. Abstract : A twofold enhancement of negative thermal expansion (NTE) coefficient has been achieved in a polymer system containing S‐dibenzocyclooctadiene. Varying the degree of molecular structural randomness, tunable NTE has been attained. Experimental and theoretical analyses indicate that molecular randomness results in a loosely packed morphology and consequently facilitates the S‐dibenzocyclooctadiene conformation change. These materials can be exploited for multiple applications.